Association of relative hand grip strength with myocardial infarction and angina pectoris in the Korean population: a large-scale cross-sectional study - Jeong Hee Chi; Bum Ju Lee (BMC, 2024)
Abstract Background Low hand grip strength (HGS) is associated with the risk of cardiovascular diseases, but the association between HGS and myocardial infarction/angina pectoris (MIAP) is unclear. Furthermore, there have been no studies examining the associations of MIAP with anthropometric indices, absolute HGS indices, and relative HGS indices calculated by dividing absolute HGS values by body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), or weight values. Therefore, the objective of this study was to examine the associations of MIAP with absolute and relative HGS combined with several anthropometric indices. Methods In this large-scale cross-sectional study, a total of 12,963 subjects from the National Health and Nutrition Examination Survey were included. Odds ratios and 95% confidence intervals for the associations of MIAP with anthropometric indices, absolute HGS indices, and relative HGS indices were computed from binary logistic regression models. We built 3 models: a crude model, a model that was adjusted for age (Model 1), and a model that was adjusted for other relevant covariates (Model 2). Results For men, the average age was 61.55 ± 0.16 years in the MIAP group and 66.49 ± 0.61 years in the non-MIAP group. For women, the average age was 61.99 ± 0.14 years in the MIAP group and 70.48 ± 0.61 years in the non-MIAP group. For both sexes, the MIAP group had lower diastolic blood pressure, shorter stature, greater WC, and a greater WHtR than did the non-MIAP group, and women tended to have greater systolic blood pressure, weight, and BMI than in men. HGS was strongly associated with the risk of MIAP in the Korean population. In men, relative HGS indices combined with WC and the WHtR had greater associations with MIAP than did the anthropometric indices and absolute HGS indices. However, in women, anthropometric indices, including weight, BMI, WC, and WHtR, were more strongly associated with MIAP than were absolute and relative HGS indices, unlike in men. When comparing absolute and relative HGS indices in women, relative HGS indices combined with BMI and weight was more strongly related to MIAP than was absolute HGS indices. Conclusions MIAP might be better identified by relative HGS than absolute HGS in both sexes. The overall magnitudes of the associations of MIAP with absolute and relative HGS are greater in men than in women.